Factors Influencing Purchase Intention for Electric Motorcycles in Indonesia: An Integrated Theory of Planned Behavior–Technology Acceptance Model Approach - Budi Oktavianus Yusan; Marcellia Susan; Anny Nurbasari (Journal of Social Research, 2026)
This study examines Indonesian consumers' intention to purchase electric motorcycles by identifying the factors that influence it, using an integrated Theory of Planned Behavior (TPB)–Technology Acceptance Model (TAM) framework. A cross-sectional survey (n = 143) was conducted, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model showed acceptable reliability and validity. The findings revealed that attitude was the strongest direct predictor of purchase intention (? = .353), followed by subjective norms (? = .315) and perceived behavioral control (? = .214), explaining 54.7% of the variance in intention (R² = .547). Technology beliefs influenced intention indirectly through TPB pathways: perceived usefulness strongly predicted attitude (? = .709), while perceived ease of use positively predicted perceived behavioral control (? = .490), supporting both mediation effects. The model also demonstrated predictive relevance in cross-validation. Theoretically, the study extends TPB–TAM evidence to Indonesia's two-wheeler context by showing that TAM beliefs operate through attitude and control. Practically, the findings suggest three levers to raise purchase intention: quantified value communication (e.g., total cost of ownership, reliability, daily convenience), friction reduction (test rides, charging and service enablement), and social-proof activation (peer/community endorsement).